Non-Ordinary Mental Expressions - Enrico Facco (Frontiers Research Topics, 2015)
So-called altered states of consciousness (ASC) are an intriguing, still under-researched topic, with profound neuropsychological and epistemological implications. In the last few decades there has been increasing multidisciplinary interest in consciousness and ASC, a term encompassing a wide range of pathological and non-pathological conditions, including dreaming, near-death experiences (NDEs), hypnagogic states, hallucinogenic experiences, epileptic seizures, psychotic symptoms, coma, and minimally conscious states. There has also been considerable research on procedures that may affect ASC including hypnosis and various forms of meditation. Since the term altered implies for some abnormality or dysfunction, the concept of anomalous experiences (not necessarily implying pathology) is increasingly used and more general. The term non-ordinary mental expressions (NOME) encompasses both anomalous (at least for a particular culture at a particular time) experiences and related neuropsychological processes and induction procedures. Our use of non-ordinary: a) does not assume pathology; and b) is suitable for sophisticated and positive mental activities, including, creativity, intuition, and some forms of spirituality. We use the term mind to include both conscious and preconscious processes, and question the notion that, "ordinary", waking consciousness provides the only epistemologically valid stance with regard to the mind and its interactions with reality. Similarly, although genius and madness both imply something beyond normal, they differ importantly in their ontology and implications. In short, NOME refers to both experiences and procedures that seek to change short- or long-term psychological processes. Regarding the latter, meditation is an intentional activity, calling for training of attention and reflective awareness, and varying in specific procedures and outcomes. With regard to an absence of pathology, NDEs, which have several features in common with mystical experiences, may occur in the absence of any brain disorder and bring about positive changes. Reductionist interpretations of NDEs as pathophysiological do not explain nor encompass the whole range of their phenomenology. Instead, brain areas and neurotransmitters potentially involved in these experiences may provide a common terrain for both pathological and non-pathological mind expressions. We believe that a proper approach to NOME should adopt a neurophenomenological approach to the study of brain mechanisms and subjective experiences as a whole, integrating experiential and neuroscientific perspectives, without any a priori fixed hierarchy or ontology. The brain-mind relationship can be analyzed as a recursive loop, where brain activity gives rise to mental phenomena and mental processes, in turn, yield functional and plastic changes in the brain. This Research Topic will include international experts in NOME as well as young researchers within a multidisciplinary discussion, in which neuroscientists, psychologists, psychiatrists, philosophers, anthropologists, and other professionals will be asked to contribute. We aim to reappraise the importance of NOME and its implications for the mind-brain-world relationship. The editors will solicit original research contributions as well as theoretical papers, such as reviews, mini-reviews, and theoretical discussions.